2011
DOI: 10.1016/j.cellsig.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of the EphA2 receptor with a serine/threonine phosphatase suppresses the Akt-mTORC1 pathway in cancer cells

Abstract: Receptor tyrosine kinases of the Eph family play multiple roles in the physiological regulation of tissue homeostasis and in the pathogenesis of various diseases, including cancer. The EphA2 receptor is highly expressed in most cancer cell types, where it has disparate activities that are not well understood. It has been reported that interplay of EphA2 with oncogenic signaling pathways promotes cancer cell malignancy independently of ephrin ligand binding and receptor kinase activity. In contrast, stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 82 publications
6
103
1
Order By: Relevance
“…(52), which could in turn impair downstream activation of Akt and/or Rac. Alternatively, ephrin-A1 could activate a serine/ threonine phosphatase, which could inhibit Akt and/or mTOR function, as recently described by Yang et al (74). Further investigation is required to identify the precise target of inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…(52), which could in turn impair downstream activation of Akt and/or Rac. Alternatively, ephrin-A1 could activate a serine/ threonine phosphatase, which could inhibit Akt and/or mTOR function, as recently described by Yang et al (74). Further investigation is required to identify the precise target of inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…36 EphA2 activation also decreased proliferation in breast cancer cells and in prostate carcinoma cells by inhibiting phosphorylation of serine/threonine protein kinase Akt. 37,38 On the other hand, it was demonstrated that the expression of EphA2 is associated with increased tumor cell proliferation in cutaneous melanoma. 39 The influence of EphA2 activation on the cytoskeleton and, hence, on adhesion, migration and metastasis is under intensive investigation and several involved signaling pathways have been identified so far.…”
Section: Do Not Distributementioning
confidence: 99%
“…[1][2][3][4][5][6][9][10][11][12][13][14][15][17][18][19]37,38) Of note, in some types of cells, the canonical pathway was reported to promote ERK activation via SH2-coutaining collagen-related proteins (SHC) and growth factor receptor-bound protein 2 (GRB2). 39) This disparity highlights how the cell type and cell microenvironment affect signaling.…”
Section: Basic Structure Of Epha2 and Epha2 Canonical Pathwaymentioning
confidence: 99%